Condições de financiamento reembolsável à inovação do setor de tecnologia de informação de Minas Gerais - Tatielle Menolli Longhini (2016)
Innovation is essential for competitiveness and global economic development. The sector (IT) Information Technology excels in the practice of innovation, depending on the speed of evolution of knowledge. In Brazil, there are few investments in innovation by the private sector, being allocated to promoting innovation in the public sector. Specifically in the state of Minas Gerais, repayable possible lines of credit are made through the Development Bank of Minas Gerais (BDMG) for the various sectors of the local economy. The IT industry, depending on the complexity of the project evaluation, high-risk operation and the difficulty of understanding the concepts, has the highest rate of accepted and rejected proposals involving BDMG analysis on each line refundable. This document describes the conditions reimbursable financing innovation in the IT sector in Minas Gerais. The methodology includes analysis of the contents of semi-structured interviews aimed at entrepreneurs, experts and analyst BDMG innovation. Moreover, literature directed by configuring therefore a qualitative analysis. This study identified as major outcomes of the difficulties in the appropriate framework: different concepts of innovation, lack of understanding of the criteria and conditions BDMG settlements. companies that limits the granting of real guarantees of results and obtain post lines set by interest rates in the long term also read. The qualitative analysis suggests the need to develop specific reimbursable lines for the sector and the development of evaluation criteria specific segment.